If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v + 1 = 125 Reorder the terms: 1 + v = 125 Solving 1 + v = 125 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + v = 125 + -1 Combine like terms: 1 + -1 = 0 0 + v = 125 + -1 v = 125 + -1 Combine like terms: 125 + -1 = 124 v = 124 Simplifying v = 124
| 11t+6c=27 | | 42=-6x+x-8 | | 11+6=27 | | 5y-1/2=3y-5/2 | | 7.5=(5-2x)(7+x) | | 100-3t=10 | | 2x(3x-7)(2x+5)=0 | | -7+5x-3x+5x=40 | | -2[G+2]=10 | | 3-7x+3x+9=31 | | 4x^2+4.65x=.65 | | 2a-5=24 | | -99=-11y | | 9x-(9-3x)=3x-1 | | 3x+3+4x+3=52 | | 2[x-3]=x+8 | | 14=-r/8 | | 6x^2+49=-6x-14 | | 2[2m+2]=14 | | 1/2x4/9= | | 5/6*84 | | 7a+9a=4 | | 2m-1=25 | | 16=m/19 | | -3x-9x= | | -2=b/20 | | X-30=-17 | | 9+4x=5x+4 | | 11=-2[p-3] | | -9u+9u-2= | | 9=b+17 | | x^4-49+2x^2-14=0 |